Deep-water marine Rusophycus and Cruziana from the Ordovician Lotbiniere Formation of Quebec - Pickerill, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
Specimens of Rusophycus isp. and Cruziana isp. preserved on a slab collected from talus of the late Middle Ordovician Lotbiniere Formation exposed at Montmorency Falls, northeast of Quebec City, are figured and described. Post-Ordovician benthic trilobites, in marine scenarios the presumed producers of such ichnotaxa, were restricted to generally shallow-water ecological niches. Older trilobitc taxa inhabited a wide spectrum of environments, as also reflected in the occurrence of these ichnotaxa in the Lotbiniere Formation. Occurrence of these ichnotaxa in the Lotbiniere Formation, an undoubted basinal microflysch sequence, suggests that caution should be exercised, when occurring in isolation, with respect to the palaeoenvironmcntal significance of these ichnotaxa, particularly in strata of Cambrian and Ordovician age. A non-random and, instead, an interpreted rheotactic orientation of Rusophycus suggests the existence of bottom currents during production of the traces.